Survival Advantage of Upfront Surgery for Pancreatic Head Cancer Without Preoperative Biliary Drainage - Pande, Rupaly; Hodson, James; Marudanayagam, Ravi; Chatzizacharias, N.; Dasari, Bobby; Muiesan, Paolo; Sutcliffe, Robert P.; Mirza, Darius F.; Isaac, John; Roberts, Keith J. (Frontiers in Oncology, 2020)
Introduction Level 1 evidence from randomised trials demonstrates less complication when jaundiced patients with resectable pancreatic cancer proceed directly to surgery, rather than undergo preoperative biliary drainage (PBD) first. Although ‘fast track’ surgery significantly increases the resectability rate, it is unknown whether this translates into a survival benefit. This study evaluated the effect of upfront surgery on long-term survival using an intention-to-treat (ITT) analysis. Methods Patients were identified from a prospectively maintained database, stratified according to whether or not they underwent PBD. Results Among 157 patients, 84 (54%) underwent PBD. Of these, 73% underwent surgery, compared to 100% of those without PBD (p<0.001). Reasons for not undergoing surgery were progression of cancer (N=11), progressive frailty (N=5), or PBD-related complication (N=7). In those who underwent surgery, PBD was associated with a longer time from diagnosis to surgery (median: 59 vs. 14 days, p<0.001), and a higher rate of unresectable cancer at surgery (26% vs. 3%, p<0.001). On an ITT basis, patients treated with PBD had significantly shorter survival, at a median of 15 vs. 19 months (HR: 1.59, 95% CI: 1.07 – 2.37, p=0.023). However, for the subset of patients who underwent resection, survival was similar in the two groups (HR: 1.07, 95% CI: 0.66 – 1.73, p=0.773). Conclusions A reduced time to surgery with avoidance of PBD offers survival benefit. This is only appreciated on ITT analysis, which includes patients who are initially considered candidates for surgery, but ultimately do not undergo surgery. Considering this ‘hidden’ cohort of patients is important when considering optimal pathways for the treatment of resectable pancreatic cancer.